Balancing Curriculum Intent with Expected Student Responses to Designerly Tasks - Buckley, Jeffrey; Seery, Niall (Design and Technology Education: An International Journal, 2018)
Design activities form an extensive part of design and technology education with a link being posited within the pertinent literature between the cognitive activity of learning and the cognitive activity of design. It is therefore critical that design educators’ understand the effects that design constraints can have on the learning process. This paper aims to examine the potential to affect student responses and associated learning from design tasks based on the manipulation of task variables. A study was designed to examine the effects of two modelling systems – one parametric and one non-parametric – on the thought processes and design journeys of the students. The findings suggest that the use of parametric modelling can emphasis student thinking on technical considerations while the use of a freeform moulding CAD system affords a more creative orientation. Qualitative findings demonstrate the capacity of students to select appropriate strategies to complete the design task, further indicating that relaxing design constraints can support student learning in design activities. Considering curricular intentions to develop both technical and creative competencies, this study presents empirical findings illustrating how teachers can strategically design tasks which balance expected student responses with intended learning outcomes.